SUBDIVISION OF OLIGOCENE AND LOWER MIOCENE SEDIMENTS OF NORTHERN SAKHALIN EVIDENCED BY MOLLUSKS - Barinov K.B.; Gladenkov Yu.B. (My University, 1998)
Upper Eocene, Oligocene, and lower Miocene units were distinguished in the Lower Cenozoic Machigar and Tumi formations of the Schmidt Peninsula, northern Sakhalin, using distribution patterns of 77 mollusk species. A detailed study of their assemblages permitted for the first time the subdivision of the section into nine faunal beds. The results are used to correlate the section with coeval deposits in adjacent regions and to perform paleogeographical reconstructions.
Keywords: Oligocene; Miocene; Кайнозой::Палеоген::Олигоцен; Cenozoic::Neogene::Miocene; Cenozoic::Paleogene::Oligocene; Кайнозой::Неоген::Миоцен